2018
DOI: 10.1177/0300060518757928
|View full text |Cite
|
Sign up to set email alerts
|

Association between Toxoplasma gondii infection and history of blood transfusion: a case-control seroprevalence study

Abstract: ObjectivesThis study was performed to determine the association between seropositivity to Toxoplasma gondii and a history of blood transfusion.MethodsPatients who had undergone blood transfusion (n = 410) and age- and sex-matched controls who had not undergone blood transfusion (n = 1230) were examined for anti-T. gondii IgG and IgM antibodies using enzyme-linked immunoassays.ResultsAnti-T. gondii IgG antibodies were detected in 57 (13.9%) patients and in 129 (10.5%) controls with a borderline difference [odds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 35 publications
2
16
1
1
Order By: Relevance
“…Previous studies demonstrated that blood transfusion was a risk factor for T. gondii infection in patients with malignancy [6,15,21]. In the current study, we found among many clinical variables, the seroprevalence of T. gondii was only associated with the history of chemotherapy.…”
supporting
confidence: 52%
“…Previous studies demonstrated that blood transfusion was a risk factor for T. gondii infection in patients with malignancy [6,15,21]. In the current study, we found among many clinical variables, the seroprevalence of T. gondii was only associated with the history of chemotherapy.…”
supporting
confidence: 52%
“…It is well documented that blood transfusion could be a potential risk factor for T. gondii infection. (59) Meanwhile, blood can be transfused frequently to pregnant women, posing those seronegative to the risk of contracting primary infections.…”
Section: Discussionmentioning
confidence: 99%
“…After infection, T. gondii can disseminate into each organ of the infected host through blood circulation [32]. Previous studies have shown that intracellular tachyzoites can disseminate into the whole body through the blood circulation, while extracellular tachyzoites do not have this ability [33, 34]. In this study, oral cancer patients with blood transfusion history had a significantly higher seroprevalence than control subjects (adjusted OR = 1.66, 95% CI: 1.18–2.32, P = 0.003).…”
Section: Discussionmentioning
confidence: 99%